2015
DOI: 10.1016/j.jcma.2015.01.010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of preprocedure anxiety levels on postprocedure pain scores in women undergoing hysterosalpingography

Abstract: According to this study, preprocedure anxiety levels have an effect on postoperative pain scores in women undergoing HSG procedure. Multiparity, male operator, and higher preprocedure anxiety scores also may have an effect on postoperative pain scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 25 publications
2
21
1
1
Order By: Relevance
“…The causes of pain felt during the procedure include the cervical traction, uterine cavity stretching and peritoneal irritation of the contrast agent (Szymusik, Grzechocińska, Marianowski, Kaczyński, & Wielgoś, ). Besides the anatomic and physical reasons, psychological factors like depression and anxiety have been reported as affecting factors in the perception of pain during gynaecological invasive procedures (Cicinelli, ; Tokmak et al, ). Anxiety is caused by the uncertainty and unfamiliarity during invasive procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The causes of pain felt during the procedure include the cervical traction, uterine cavity stretching and peritoneal irritation of the contrast agent (Szymusik, Grzechocińska, Marianowski, Kaczyński, & Wielgoś, ). Besides the anatomic and physical reasons, psychological factors like depression and anxiety have been reported as affecting factors in the perception of pain during gynaecological invasive procedures (Cicinelli, ; Tokmak et al, ). Anxiety is caused by the uncertainty and unfamiliarity during invasive procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety is caused by the uncertainty and unfamiliarity during invasive procedures. Education and counselling have been shown to be effective in reducing the anxiety and pain experienced by patients for painful invasive procedures (Balci, Acar, Mahmoud, & Colakoglu, ; Hanprasertpong et al, ; Tokmak et al, ). Only a few interventional studies aiming to lower the anxiety felt by women undergoing HSG have been found (Agwu & Okoye, ; Erkılınç et al, ; La Fianza et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The authors investigated the effect of various clinical factors and preprocedural anxiety levels on pain perception in these women after the HSG procedure and found that high preprocedure anxiety levels and male operators contributed to increased postprocedure pain in women who received HSG examination. 1 We congratulate the authors on the success of this publication.…”
mentioning
confidence: 91%
“…This prospective randomized study enrolled 109 women who underwent hysterosalpingography (HSG). 1 All patients had their anxiety levels assessed and scored using the Beck anxiety inventory. The authors investigated the effect of various clinical factors and preprocedural anxiety levels on pain perception in these women after the HSG procedure and found that high preprocedure anxiety levels and male operators contributed to increased postprocedure pain in women who received HSG examination.…”
mentioning
confidence: 99%
See 1 more Smart Citation